2022
DOI: 10.1007/s00421-022-05104-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-induced changes in hamstrings’ active muscle stiffness: effect of contraction type and implications for strain injuries

Abstract: Purpose Hamstring strain injuries may occur due to differential fatigue and compromised mechanical properties among the hamstring muscles. We examined (1) the effect of fatigue on hamstrings active muscle stiffness, and (2) whether contraction type affects active muscle stiffness changes during a submaximal fatiguing task. Methods Nine healthy males completed 99 submaximal knee flexions in isometric (ISO), concentric (CON), and eccentric (ECC) conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
(110 reference statements)
1
7
0
Order By: Relevance
“…Their study demonstrated that hamstring eccentric exercises using an isokinetic dynamometer may lead to an increase in stiffness post-exercise. On the other hand, our results also showed a significantly greater stiffness in the BFLH compared to the ST. Our findings are in line with Evangelidis et al, 47 who found the BFLH to be a more fatigable muscle compared to the ST or semimembranosus. Andonian et al 48 found that greater stiffness after strenuous exercise may be related to altered extracellular water volume.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Their study demonstrated that hamstring eccentric exercises using an isokinetic dynamometer may lead to an increase in stiffness post-exercise. On the other hand, our results also showed a significantly greater stiffness in the BFLH compared to the ST. Our findings are in line with Evangelidis et al, 47 who found the BFLH to be a more fatigable muscle compared to the ST or semimembranosus. Andonian et al 48 found that greater stiffness after strenuous exercise may be related to altered extracellular water volume.…”
Section: Discussionsupporting
confidence: 93%
“… 49 Moreover, greater mechanical alterations in BFLH compared with ST might be related to the fact that BFLH experiences the greatest strain compared to other muscles in the posterior thigh. 47 A research study performed by Seymore et al 21 showed that NHE training did not significantly affect muscle fascicle length, stiffness, or eccentric hamstring strength. Noticeable changes in muscles may be related to increased vascularity resulting from greater muscle activity during acute fatigue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maximal muscle fatigue induces heightened muscle stiffness and muscle frequency, as observed in both dominant and non-dominant legs. This insight holds pivotal significance for rehabilitation and sports performance, indicating that fatigue elicits distinct effects on specific muscle groups [ 8 ]. Rehabilitation programs and training protocols may necessitate tailored considerations for these distinctions to augment recovery and optimize performance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Evangelidis et al demonstrated that muscle fatigue significantly impacts the stiffness of the biceps femoris long-head muscle more than the semitendinosus and semimembranosus muscles, providing insight into the increased vulnerability to strain injuries within this muscle group [ 8 ]. Additionally, in the context of rehabilitation following Rotator Cuff tendinopathy, there is a manifestation of reduced tendon stiffness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%